Where Technology Meets Islam: Towards an Islamic Perspective on Technology - Ehsan Arzroomchilar; Maryam Olamaiekopaie (Journal of Islamic Thought and Civilization, 2022)
Technology is a pervasive phenomenon in our surroundings. Today, we rarely experience the natural world and our relationship with the world is most often technologically mediated. The long-standing view in the Islamic world toward technology seems to be taking it as an innocent tool which carries only instrumental value. If so, there would not arise any moral question concerning technology per se. Rather, everything would concern with the way it is used by individuals. This instrumentalist approach, however, is notoriously premature. Technology inherently is value-laden and accordingly calls for philosophical as well as moral evaluation. In this article, we will suggest a context for assessing technology from an Islamic point of view. To that purpose, we will unpack Heidegger’s account of technology to bring into relief an enduring problem associated with modern technology, the problem of Gestell. Our source of inspiration to accommodate Heidegger’s concern is the work of Tabātabā’i, the contemporary Muslim thinker, on theory of iʿtibārīat and also his contribution to the virtue ethics. In the end we will find that, according to Tabātabā’i, the problem of technology is rooted in deviation from the golden mean, in the wake of secularization of the world in the modern era. Keywords: Heidegger, Islamic Technology, Iʿtibārīat, Tabātabā'i, Technology, Virtue Ethics